Fiscal Policy Across Levels of Government in Times of Crisis - Blöchliger, Hansjörg (OECD Publishing, 2010)
The world is recovering from the worst economic and financial crisis since the Great Depression. The recovery will probably be shallow and government deficits could remain very large over the next few years in a number of countries. The crisis has a negative impact not only on central governments, but also on sub-national governments. While the situation varies from country to country, depending on the institutional environment, types of revenue sources and spending responsibilities, an increasing number of sub-national governments are facing budget imbalances, as the economic slump is putting upward pressure on spending, while pushing down tax revenues
Keywords: Taxation